2002
DOI: 10.1152/ajpcell.00609.2001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclooxygenase-2 by heat shock protein 60 in macrophages and endothelial cells

Abstract: The 60-kDa heat shock protein (HSP60), an endogenous ligand for the toll-like 4 receptor, is generated in response to inflammation, tissue injury, and/or stress and stimulates macrophages to produce cytotoxic and proinflammatory mediators including nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-12. In the present studies we report that HSP60 is an effective inducer of cyclooxygenase-2 (COX-2) in macrophages, as well as endothelial cells. In both cell types, the synthesis of COX-2 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Both ERK and JNK are required for Cox-2 promoter activity induced by IgE receptor aggregation in mast cells (74). ERK1/2 and p38 play a role in regulating HSP60-induced expression of Cox-2 in macrophages (74). Our results showed that of the three MAPKs, only p38, but not ERK and JNK, played a critical role in the CpG DNA-induced Cox-2 promoter activity (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Both ERK and JNK are required for Cox-2 promoter activity induced by IgE receptor aggregation in mast cells (74). ERK1/2 and p38 play a role in regulating HSP60-induced expression of Cox-2 in macrophages (74). Our results showed that of the three MAPKs, only p38, but not ERK and JNK, played a critical role in the CpG DNA-induced Cox-2 promoter activity (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, LPS-induced murine Cox-2 promoter activity in RAW264.7 cells is dependent on ERK (43). Both ERK and JNK are required for Cox-2 promoter activity induced by IgE receptor aggregation in mast cells (74). ERK1/2 and p38 play a role in regulating HSP60-induced expression of Cox-2 in macrophages (74).…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] HSP60 mediates its effects, in part, by binding to surface CD14 and Toll-like receptors, which are also utilized in LPS-mediated signaling and may, therein, serve as the endogenous ligand of the LPS receptor. [44][45][46][47][48] Taken together, these data suggest that HSP60 may be involved in pathologies involving inflammation.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Sense and antisense primers for RT-PCR reactions of rat Sclc2a1 and Sclc2a4 and bovine Ptgs2 were synthesised according to published sequences [30][31][32] by Sigma-Aldrich (Rehovot, Israel). Synthesis of cDNA and PCR was carried out in a PTC-100 programmable thermal controller (MJ Research, Waltman, MA, USA) as described [29][30][31][32]. The nucleotide sequence of each PCR product was identical to the predicted sequences.…”
Section: Animalsmentioning
confidence: 99%
“…Bovine aortic endothelial cells (VEC) and smooth muscle cells (VSMC), which predominantly express SCLC2A1 (GLUT1) [30], were used to investigate the potential effects of COX2 (PTGS2) inhibitors on their hexose transport capacity. Fig.…”
Section: Cox2 (Ptgs2) Inhibitors Failed To Alter the Rate Of Hexose Tmentioning
confidence: 99%